Karyological notes on another eight species of Achillea (Asteraceae) from Turkey - Kiran, Yasar; Arabaci, Turan; Sahin, Ahmet; Turkoglu, Ismail (Springer, 2008)
The chromosome number and morphology in eight species of the sections Ptarmica (Mill.) W. D. J. Koch, Anthemoideae (DC.) Heimerl, Arthrolepis Boiss., Santolinoideae (DC.) Heimerl and Achillea of the genus Achillea L. (Asteraceae) were investigated using karyological techniques. Sample plants and seeds of A. biserrata M. Bieb., A. fraasii var. troiana Aschers. & Heimerl, A. multifida (DC.) Boiss., A. brachyphylla Boiss. & Hausskn., A. pseudaleppica Hub.-Mor., A. cretica L., A. latiloba Ledeb. ex Nordm., and A. kotschyi Boiss. subsp. kotschyi) were collected from natural habitats in 2003 and 2004. The chromosome number found in seven species was 2n = 18, while only A. kotschyi had 2n = 36. All chromosomes had median point (M), median region (m), and submedian (sm) centromers. In addition, only A. biserrata species had one subterminal (st) chromosome. An increase in asymmetry was not observed in the karyotypes of the species studied. None of the studied species had any B chromosomes.
Keywords: Achillea; chromosome number; karyotypes; mitosis; Turkey